FORMULASI DAN KARAKTERISASI FISIK MASKER GEL PEELOFF EKSTRAK LENGKUAS (Alpinia galanga, (L.) Sw) - Mar’atus Sholikhah; Rahayu Apriyanti (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2019)
ABSTRACT Alpinia galanga (L.) Sw or galangal is widely used by Indonesian people as a spice in cooking. The content of catechins and 1-acetoxicavicol acetate in the extract is known to have antioxidant activity. The ability of these antioxidants needs to be applied to pharmaceutical dosage forms to improve aesthetics and ease of use. One of the topical drug delivery systems that is in accordance with the needs of the community today is the preparation of peel-off gel mask. The purpose of this study was to determine the effect of variations in PVA gelling agent concentration as a mask base on the physical characteristics of galangal extract peel-off gel masks. Three mask formulations were made based on variations in the concentration of PVA in the range of 5% -15%. The physical characterization of the preparations included organoleptic tests, homogeneity, pH, viscosity, adhesion, dispersion, and drying time. Homogeneity and organoleptic parameters were analyzed descriptively. The parameters of viscosity, drying time, pH, spreadability, and adhesion were analyzed statistically using Anova Single Factor with a confidence level of 95%. The results showed that the F1 and F2 formulas with PVA concentrations of 10% and 12.5% were the optimum formulas as a mask base. Based on statistical tests, variations in the concentration of PVA significantly influence the parameters of mask adhesion with a p-value of 0.0001 (